2004
DOI: 10.2355/isijinternational.44.482
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Behaviour of Cement-bonded Briquettes-proposed Model

Abstract: The cement-bonded agglomeration process is an alternative to the traditional balling-sintering process for recycling iron-rich by-products generated in iron and steel plants back to the blast furnaces. It has been observed that, under certain conditions, the briquettes containing pellet-fines show a tendency to swell catastrophically when reduced. This swelling is dependent upon a number of factors like: reducing temperature, composition of briquettes, particle size of raw material, amount of cement and compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…At 850°C, the iron oxides are reduced to metallic iron. At 1 100°C, the metallic iron became the dominant phase in the reduced samples beside slag (CaO, CaSiO 4 and CaMgSiO 4 ). The intensity of metallic iron in lignin samples (R3) is higher than that in reference sample (R1) which confirms the positive impact of lignin on the reduction rate of iron oxides.…”
Section: Reduction Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…At 850°C, the iron oxides are reduced to metallic iron. At 1 100°C, the metallic iron became the dominant phase in the reduced samples beside slag (CaO, CaSiO 4 and CaMgSiO 4 ). The intensity of metallic iron in lignin samples (R3) is higher than that in reference sample (R1) which confirms the positive impact of lignin on the reduction rate of iron oxides.…”
Section: Reduction Behaviourmentioning
confidence: 99%
“…[1][2][3] Under normal conditions cement is used as a binder to give the proper mechanical strength of the briquettes and then it goes to slag during the production of hot metal. [4][5][6] Coke and coal are the main sources of fuel and reducing agent in the blast furnace, at the same time they are responsible for the main fossil CO 2 emission in steel industry. Intensive work is being done to mitigate the CO 2 emissions in steel industry by partial substitution of fossil fuels (coal and coke) with renewable source of energy such as biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Swelling can be categorized into normal swelling, up to 20% in volume, [1][2][3][4][5] and abnormal, i.e. catastrophic swelling, which may exceed 400% in volume at worst.…”
Section: Introductionmentioning
confidence: 99%
“…2) Various operating parameters such as firing time, rate of reduction, reduction temperature, reduction time, reducing gas atmosphere, partial pressure of reducing gases, total flow rate, impurities in the reducing gas and isothermal/nonisothermal reduction, and pellet properties such as porosity, basicity and gangue content, have been reported to affect the swelling of different pellet types used in blast furnaces. [1][2][3][4][5][6][7] Some authors 10,11) have reported the existence of a critical rate of reduction at which the swelling index of an iron oxide pellet reaches its maximum value. In addition, sulphur 6,22,23,25) and potassium 22) in the reducing atmosphere have been associated with the swelling of pellets.…”
Section: Introductionmentioning
confidence: 99%
“…Singh and Bjorkman [23][24][25] studied the effect of reduction conditions on the swelling behavior of cement-bonded briquettes. It was observed that, under certain conditions, the briquettes containing fines generated from pellets during handling show a tendency to swell catastrophically when reduced at 900-1 000°C using CO.…”
Section: Introductionmentioning
confidence: 99%